Comparative survival analysis using the International Stratification Score (ISS) in newly-diagnosed multiple myeloma in the Uruguayan population - Garrido, David Israel; Bove, Virginia; Matosas, Victoria; Riva, Eloisa (Medicine and Pharmacy Reports, 2021)
Background and aims. Multiple myeloma is a frequent hematologic malignancy, in which the International Stratification Score (ISS) is widely used to estimate the overall survival. However, there are no studies in Latin America evaluating its performance. This study aims to describe the ISS performance in the overall survival estimation for newly diagnosed multiple myeloma patients in Uruguay. Methods. This is a retrospective registry‐based survival analysis through the Grupo Uruguayo de Mieloma Múltiple (GUMMA) database, including newly diagnosed multiple myeloma patients from January 2001 until May 2019. Results. 249 patients were included, 51.81% males and an average age of 63.49 years. According to ISS and Durie-Salmon score (DSS), 47.79% and 82.3% were ISS III and DSS III, respectively. Also, 32.3% were DSS B. Auto hematopoietic stem cell transplantation was performed in 31.73% of patients, and bortezomib was used in 44.18% as frontline therapy. The overall survival was 80% for ISS1, 64.9% ISS2, and 48.6% ISS3 (Log-Rank; p <0.01). The average overall survival was 116.5 months for ISS 1, 77.6 months for ISS 2, and 57.8 months for ISS 3. The hazard ratio between ISS II and ISS I was 2.42 (95% CI 1.10-5.33; p<0.05), and 3.94 (95% CI 1.88-8.26; p<0.05) between ISS III and ISS II. Conclusion. The ISS staging system allows an adequate stratification of patients according to overall survival in the real-practice setting. However, considering the relevance of the new cytogenetic advances, it is necessary to increase the availability and quality of iFISH in Latin America.